Framework Breathing in the Vapour-Phase Adsorption and Separation of Xylene Isomers with the Metal-Organic Framework MIL-53 - Finsy, Vincent; Kirschhock, Christine E. A.; Vedts, Gill; Maes, Michael; Alaerts, Luc; De Vos, Dirk E.; Baron, Gino V.; Denayer, Joeri F. M. (Chemistry : a European journal, 2009)
Vapour‐phase adsorption and separation of the C8 alkyl aromatic compounds p‐xylene, m‐xylene, o‐xylene, and ethylbenzene has been studied on the metal–organic framework MIL‐53. Adsorption and desorption isotherms of the pure components at 110 °C were determined using the gravimetric technique. The adsorption isotherms show two well‐defined steps and hysteresis, corresponding to the opening or breathing of the framework, as induced by the presence of the adsorbing molecules. In the first isotherm plateau, an adsorption capacity of about 18 wt % is observed. After the breathing phenomenon, the adsorption capacity increases to about 40 wt %. Breakthrough separation experiments with equimolar o‐xylene/ethylbenzene mixtures were performed at 110 °C with varying hydrocarbon pressures. The separation mechanism is related to the state of the pore structure, as dictated by framework breathing. At low pressure, below the “pore‐opening” pressure, MIL‐53 shows no preference for any isomer. At pressures high enough to induce pore opening, separation of the C8 alkyl aromatic isomers becomes possible and separation factors as high as 6.5 are observed. The separation at a high degree of pore filling in the open form is a result of differences in the packing modes of the C8 alkyl aromatic components in the pores of MIL‐53. Isomer separation on MIL‐53: Framework breathing permits separation of xylene isomers (see picture). At low pressures (top), adsorption of C8 alkyl aromatic compounds induces contraction of the MIL‐53 (Al) framework. Under these conditions, there is no difference in adsorption between the various isomers. No separation is possible. At higher pressures (bottom), the framework is reopened and additional molecules are adsorbed in a selective way.